2021
DOI: 10.1002/ps.6385
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sublethal and transgenerational effects of sulfoxaflor on Aphis gossypii via life table parameters and 16S rRNA sequencing

Abstract: BACKGROUND: Aphis gossypii, a polyphagous and recurrent pest induced by pesticides, causes tremendous loss crop yields each year. Previous studies on the mechanism of pesticide-induced sublethal effects mainly focus on the gene level. The symbiotic bacteria are also important participants of this mechanism, but their roles in hormesis are still unclear.RESULTS: In this study, life table parameters and 16S rRNA sequencing were applied to evaluate the sublethal and transgenerational effects of sulfoxaflor on adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 78 publications
2
29
0
Order By: Relevance
“…For example, Ullah et al [ 46 ] found an LC 15 concentration of acetamiprid significantly reduced the longevity and fecundity of the parent generation (F 0 ) A. gossypii . Shang et al [ 47 ] found that the longevity of the parent generation (F 0 ) of A. gossypii was significantly prolonged and the fecundity was higher in response to an LC 20 concentration of sulfoxaflor. Sublethal concentrations (LC 10 and LC 25 ) of sulfoxaflor significantly inhibited the longevity and the fertility of M.persicae (F 0 ) [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Ullah et al [ 46 ] found an LC 15 concentration of acetamiprid significantly reduced the longevity and fecundity of the parent generation (F 0 ) A. gossypii . Shang et al [ 47 ] found that the longevity of the parent generation (F 0 ) of A. gossypii was significantly prolonged and the fecundity was higher in response to an LC 20 concentration of sulfoxaflor. Sublethal concentrations (LC 10 and LC 25 ) of sulfoxaflor significantly inhibited the longevity and the fertility of M.persicae (F 0 ) [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…31 Raw fastq files were trimmed, assembled, and filtered as previously reported. 21 The high-quality sequences obtained were used for further analysis, and operational taxonomic units (OTUs) were clustered on 97% sequence similarity by using the USEARCH (version 10.0). 32 The RDP CLASSIFIER was used to classify and analyze each 16S rRNA gene sequence against the Silva database (Release128, http://www.arbsilva.de).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The V3–V4 regions of 16S rRNA were amplified using 338F (5′-ACTCCTACGGGAGGCAGCA-3′)/806R (5′-GGACTACHVGGGTWTCTAAT-3′) primers . PCR amplification, quantitation, and identification and PCR product mixed purification and library preparation were carried out as previously described, and sequencing was performed on an Illumina Hiseq 2500 platform of Biomarker Technologies Co., Ltd. (Beijing, China). The sequence obtained was stored in the GenBank SRA database with accession number PRJNA689863.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations